Integration of Malay Cultural Values in Islamic Education: An Analysis of Local Values-Based Contextual Approach - Sari, Khovifah Puspita; Soraya, Nyayu; Anggara, Baldi (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
This study aims to analyze the integration of Malay cultural values in Islamic education through a contextual approach based on local culture (Contextual Teaching and Learning/CTL). Malay culture possesses its own noble values, such as politeness, respect for social hierarchy, mutual cooperation, and the principle of adat bersendi syarak, syarak bersendi Kitabullah. All of which are aligned with the teachings of Islam. Although many studies have discussed Islamic education and local culture, research that specifically examines the integration of Malay cultural values within the CTL learning framework remains limited. Therefore, this study aims to fill this research gap through the conceptual and theoretical analysis. This is a library research using a qualitative descriptive approach by analyzing various relevant scholarly sources on Malay culture, Islamic education, and CTL theory. The findings indicates that Malay cultural values can be conceptually structured as a foundation for integration within the curriculum and instructional strategies of Islamic education. This integration had the potential to strengthen the development of students’ religious and social character while also contributing to the preservation of Malay cultural identity in the educational context. This study was theoretical in nature. It is expected to enrich the body of knowledge in Islamic education and serve as a foundation for future empirical research.